Pengembangan Model Pengasuhan Keluarga Dalam Upaya Meningkatkan Kecerdasan Emosi Dan Kemandirian Anak-Remaja Di Kabupaten Karangasem Dan Kota Denpasar - Ni Luh Putu Yunianti Suntari Cakera; I Ketut Labir (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2017)
At the present time, it is found that there are fundamental changes in almost all families. Many reported cases found discriminating women and children. In discussing children, there are many violations to the safeguard of children. And it happened in their families. Problems occur due to many factors, among others, the increasing role of older people in society, ignorance of the family in performing care for children in the current circumstances. Parents need guidance and direction in helping their children to grow and develop. This study aims to find a simple guide to help parents exercising their role optimally in order to protect children and help them to grow in intelligence and independence. A provision needed by children to face their future. Based on the above background, it can be formulated research problem which is